Comparison of Nigerian Fermented Food Condiments - Osuagwu, A. N.; Amusan, B. B. (Journal of Science, Technology and Innovation Research, 2026)
Food condiments in Nigeria are consumable ingredients added to meals to improve their taste, aroma or consistency. This research was conducted to evaluate and contrasts the phytochemical content, mineral element, vitamins levels, and overall nutritional value of ogiri okpeyi, ogiri and dawadawa. The analyses were performed in accordance with standard procedures outlined by the Association of Official Analytical Chemists (AOAC). The moisture levels observed in ogiri okpeyi, ogiri and dawadawa varied between (11.20a ± 0.28-4.50b± 0.14). The fat levels of the condiments were found to fall within a range of (7.80b ± 0.00-28.60a±0.28). The ash ranged from (3.30a± 1.27 – 4.70a ± 0.14). The fibre, protein and carbohydrate ranged from 2.20b ± 0.00-65.85a ± 1.13. The mineral content of the three food enhancer varied from (3.67b ± 0.16 – 313.05a ± 0.38). The vitamin composition ranged from (0.13a ± 0.01-9.48a ±0.53). The phytochemical content of all three samples investigated ranged from (0.23c±0.00-4.23 ± 0.00). The nutritional result revealed that ogiri had the highest nutritional content compared to others. Ogiri had the highest tannin. Flavonoid, alkaloid and phenol were highest in dawadawa. The highest saponin component was found in okpeyi. Calcium, potassium, sodium, phosphorus and iron were highest in ogiri. Magnesium was highest in Okpeyi. Vitamin E, beta-carotene, vitamin B1, and B2 were highest in ogiri, while dawadawa had the highest vitamin C. The use of ogiri should be encouraged because it has the highest nutritional content. Further studies should be done on the microbial quality of ogiri to know how safe it is for consumption.